2016
DOI: 10.1128/jcm.01053-16
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium Prevalence, Coinfection, and Macrolide Antibiotic Resistance Frequency in a Multicenter Clinical Study Cohort in the United States

Abstract: The prevalence rates of Mycoplasma genitalium infections and coinfections with other sexually transmitted organisms and the frequency of a macrolide antibiotic resistance phenotype were determined in urogenital specimens collected from female and male subjects enrolled in a multicenter clinical study in the United States. Specimens from 946 subjects seeking care from seven geographically diverse clinical sites were tested for M. genitalium and for Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

35
131
7
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(175 citation statements)
references
References 37 publications
35
131
7
2
Order By: Relevance
“…Irrespective of the specimen type used, M. genitalium was more common than any of the four other STIs (15.3% with meatal swab and 12.6% in urine) and self-sampling using a meatal swab yielded higher prevalence of all five STIs. Although assays to detect mutations in the QRDR were not performed, MRMM were detected in 55.9% of urine specimens with readable 23S rRNA sequences, consistent with an earlier report of 50% in US men and women [6]. …”
supporting
confidence: 87%
“…Irrespective of the specimen type used, M. genitalium was more common than any of the four other STIs (15.3% with meatal swab and 12.6% in urine) and self-sampling using a meatal swab yielded higher prevalence of all five STIs. Although assays to detect mutations in the QRDR were not performed, MRMM were detected in 55.9% of urine specimens with readable 23S rRNA sequences, consistent with an earlier report of 50% in US men and women [6]. …”
supporting
confidence: 87%
“…This is due to recruitment of women with or at high risk for C. trachomatis within a single geographic location. In a general population of low-risk and high-risk clinics/hospitals, Getman et al 10 reported that 68.7% of females with M. genitalium had monoinfection (absence of C. trachomatis , N. gonorrhoeae and T. vaginalis ). After treatment, the C. trachomatis coinfection rate for incident M. genitalium was 6.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent report suggests that inclusion of multiple analytes and specimen source collections significantly increases detection of STI carrier status (33). Further investigations may be necessary to indicate targeted demographics (20,(28)(29)(30) should a fully comprehensive screening approach not be advocated in a given locale. Consideration of M. genitalium molecular diagnostics within an STI screening algorithm may ultimately realize public health benefits and improved clinical management.…”
Section: Discussionmentioning
confidence: 99%